Relationship of Mom Behavior in Maintaining Dental and Mouth Health Towards The Prevention of Dental Caries in Preschool Children Aged 4-6 Years at Tunas Bangsa Tk, Tulungagung Village, Bojonegoro District 2021 - Sri Luluk; Nur Azizah; Wiwik Muhidayati; Rina Utami (Jurnal MIDPRO, 2021)
Dental care is needed by all individuals, both children and adults. In Indonesia, dental and oral diseases, especially caries and periodontal disease, are still suffered by both children and adults. The main problems of dental health, namely cavities (dental caries), malocclusion and periodontal disease, trauma and tooth loss cause parents to misperceive dental problems regarding dental caries. From the results of a preliminary study conducted by researchers, it was found that there were 5 children who had dental caries. This type of research is quantitative using a cross sectional approach. The sample in this study were all mothers who have children aged 4-6 years in Tunas Bangsa Kindergarten, Tulungagung Village, Baureno District, Bojonegoro Regency with a sample of 37 respondents and using purposive sampling technique. Data were processed using univariate, bivariate and chi-square methods. The results of the Chi Square test analysis of maternal behavior in maintaining oral and dental health on efforts to prevent dental caries in preschool children obtained a p value = 0.044 with a value = 0.05. The behavior of mothers who did not prevent and did not prevent as many as 16 people (76.2%), the behavior of mothers who did not prevent as many as 5 people (23.8%), and the behavior of mothers who were good and did not prevent as many as 7 people (43.8%), and good mother behavior and prevent as many as 9 people (56.3%). This shows that there is a relationship between maternal behavior in maintaining dental and oral health and efforts to prevent dental caries. The advice that can be given is that mothers should pay more attention to their children's dental and oral health, especially preschoolers, monitor the food consumed by children.